(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The purpose of the article is to study the current state of the legal mechanism of trade and industrial group innovative development state regulation in Ukraine. The methodological basis of the work is a structural and functional analysis of regulations of Ukraine with the aim to determine the modern principles, structure and functions of the regulatory mechanism of trade and industrial group innovative development state regulation in Ukraine. The study allowed the author to determine the legal basis for the existence, regulation and innovative development of trade and industrial groups, the theory and practice of application of the regulatory mechanism of state regulation. The study has found that most of the documents that make up the legal mechanism are descriptive and declarative in nature, are mostly focused on command-and-control principles of public regulation, do not take into account the principles of public-private partnership and do not meet the requirements and challenges of today. The existing imperfection of the regulatory framework leads to inconsistencies of public and private interests, creates a basis for irrational use of resources, threatens the state with a loss of economic, scientific and technological potential. According to the results of the study, it is proposed to audit the existing legal field concerning innovation development, adapt regulatory documents to current challenges and requirements of today, harmonize regulations, normalize gaps in the current legislative field to improve the establishment and operation of innovation infrastructure, and develop guidelines about establishment and operation of such infrastructure, which would be based on the principles of public-private partnership.